Isu Pendidikan Islam di Era Global - Nanang Anshori; Sukari Sukari (Lembaga Yasin AlSys, 2026)
Islamic education in the era of globalization faces significant changes influenced by developments in technology, information, and communication. Globalization brings positive impacts as well as challenges that require Islamic education to maintain its Islamic identity while adapting to the demands of the times. This study aims to examine issues in Islamic education in the global era, including its concepts, challenges, impacts, and opportunities for development. This study uses a qualitative approach with a library research method. Data were obtained from various relevant books and scholarly articles and were then analyzed using the Miles and Huberman interactive analysis model through the stages of data reduction, data presentation, and conclusion drawing. The results show that Islamic education is required to integrate Islamic values with modern science and technology. The main challenges faced include the influence of global culture, moral crisis, developments in information technology, limited quality of human resources, and the demands of 21st-century competencies. On the other hand, globalization also provides opportunities in the form of easier access to knowledge, innovation in learning methods, improvement in the quality of human resources, and strengthening of global educational networks. The conclusion of this study affirms that Islamic education needs to carry out curriculum innovation, utilize digital technology, integrate knowledge, and strengthen character education in order to produce a generation that is religious, has noble character, and is competitive in facing global challenges. The implications of this study indicate the importance of developing Islamic education that is adaptive, integrative, and oriented toward character formation in responding to the dynamics of globalization.